Groundwater management system using hydrogeological model in Sg. Kelantan river basin / Wan Mohd Zamri W Ismail - Wan Mohd Zamri, W Ismail (2011)
The groundwater resources of the Sg.Kelantan river basin are the main sources of fresh water and also are vitally needed to supplement surface water sources. However, despite their importance, the groundwater resources are under stress of exploitation and contamination. The maintenance and protection of groundwater ecosystems should therefore be a major topic in the coming years in groundwater water management. The main objectives of this study are to better understand the importance of a balanced development of groundwater as to preservation of good ecosystems in Kelantan by establishment of “Groundwater Resource Management (GWRM)” system, a decision support tool with GIS and database system to handle and store all water resource relevant information, and to establish a monitoring system with observation wells for level and quality of groundwater by evaluation of all existing use of water and redefine sustainable use and regulate rate of abstraction. Groundwater flow modeling of the alluvial aquifer is needed to support the sustainable groundwater management. Groundwater sources will be better managed and future development plans for groundwater will be fully controlled within the limits for a safe and sustainable environment, with following activity plan, i.e:- a) Groundwater survey, groundwater model, test drilling and pumping, and water sample analyzing in order to establishing “Groundwater Resource Management (GWRM)” system with support of GIS and database system to handle and store all water resource relevant information, b) Evaluate all existing use of water and redefine sustainable use and regulate rate of abstraction, and c) Establish a monitoring system with observation wells for level and quality of water. A validated groundwater flow model was created for a groundwater sub-basin within the north Kelantan regional groundwater basin to support the water resources management in the Kelantan State. Future development of groundwater can be guided by implementation of GWRM system and functions to safeguard any further contamination in a regional basis. This can benefits water operators and water stakeholders in understanding and managing the groundwater resources in the study area particularly.